Brachial plexus tuberculosis: A unique neurological variant of a common clinical disease (Indian Journal of Case Reports, 2021)
Isolated primary tuberculous involvement of the brachial plexus has not been reported in the past. Here, we report the case of a 29-year-old male who developed neck pain and radiculopathy for 3 months. Weakness in the left shoulder-elbow (2/5 MRC grade) and wrist (4/5 MRC grade) was present with numbness to pain and temperature along the C4–C5 dermatome. Magnetic resonance imaging (MRI) revealed a T2 hyperintense heterogeneously contrast-enhancing lesion involving the upper trunk of the brachial plexus. Under suspicion of malignancy, surgical exploration was undertaken. Intraoperatively, pus was noticed with unhealthy granulation tissue extending along the left-sided C4–5 lamina and transverse process. The frozen section suggested granulomatous infection and histopathology confirmed tuberculosis (TB). After 18 months of antituberculous treatment, the patient gradually recovered complete strength in the left upper limb. Follow-up brachial plexus MRI showed near-complete resolution of the lesion. We describe a unique case of a young patient clinically suggestive of the rapid progressive lesion (mimicking malignancy) affecting brachial plexus, turning out as TB on histopathology.